Perbedaan Asupan Lemak Dan Kebiasaan Olahraga Pada Siswa Dengan Status Gizi Overweight Dan Non-Overweight Di Smk Muhammadiyah 2 Surakarta - Ardyana, Della; , Muwakhidah, SKM, M.Kes; , Wahyuni, SSt. FT. M.Kes (2016)
INTRODUCTION: People with overweight are more common found in adolescents in urban areas due to the consumption of an unbalanced diet and lack of physical activity and exercise. The accumulation of fat in the body with lack of activity will lead to overweight. The prevalence of overweight in students at SMK Muhammadiyah 2 Surakarta 18.5%. OBJECTIVE: This study aims to determine the differences of fat intake and exercise habits between overweight and non - overweight students at SMK Muhammadiyah 2 Surakarta. METHODS: This study was an observational study with cross sectional approach. Data collected include fat intake, exercise habits and nutritional status of overweight and non-overweight of students. Fat intake was measured using food recall form for 7 consecutive days. Exercise habits taken using a questionnaire of exercise habits. Total sample were 41 overweight and 41 non-overweight students. Analysis of data using Independent T-test and Mann Whitney. RESULTS: The results showed that fat intake of overweight subjects categorized enough (56.1%). Overweight subjects had less exercise during the week which was 75.6%. The p-value of the difference of fat intake between overweight and non-overweight students was 0.227 and the p-value of the difference of exercise habit between overweight and non-overweight students was 0.001. CONCLUSION: There was a difference of exercise habits between overweight and non-overweight students at SMK Muhammadiyah 2 Surakarta. There was no difference of fat intake between overweight and non-overweight students.